A Randomized Controlled Trial to Assess the Efficacy of Tiotropium in Canadian Patients with Chronic Obstructive Pulmonary Disease - Charles KN Chan; François Maltais; Chris Sigouin; Jennifer M Haddon; Gordon T Ford; on behalf of the SAFE Study Group (Canadian Respiratory Journal)
BACKGROUND: Patients with chronic obstructive pulmonary disease (COPD) who smoke have a greater annual rate of decline in forced expiratory volume in 1 s (FEV1) than those patients who have stopped smoking.